The Effects of DACA on Health Insurance, Access to Care, and Health Outcomes - Osea Giuntella; Jakub Lonsky (Institute of Labor Economics (IZA), 2018)
This paper studies the effects of the 2012 Deferred Action for Childhood Arrivals (DACA) initiative on health insurance coverage, access to care, health care use, and health outcomes. We exploit a difference-in-differences that relies on the discontinuity in program eligibility criteria. We find that DACA increased insurance coverage. In states that granted access to Medicaid, the increase was driven by an increase in public insurance take-up. Where public coverage was not available, DACA eligibility increased individually purchased insurance. Despite the increase in insurance coverage, there is no evidence of significant increases in health care use, although there is some evidence that DACA increased demand for mental health services. After 2012, DACA- eligible individuals were more likely to report a usual place of care and less likely to delay care because of financial restrictions. Finally, we find some evidence that DACA improved self-reported health, and reduced depression symptoms, indicators of stress and anxiety, and hypertension. These improvements are concentrated among individuals with income below the federal poverty level.
Keywords: I10; J15; J61; 330; health insurance; DACA; immigration; health care; health